Vitality a psychiatrist's answer to life's problems - Esser, Richard (Algora Pub, 2008)
Depression, confusion, and desperation sap the energy we need to address the challenges of life; Dr. Esser shows how we can uncap a well of energy and vitality to overcome problems and turn our lives around. Optimistic and easy to read, this book gives practical new insights into how to get the best out of living and how to cope with the worst.
Keywords: Mental health; Vitality